Health knowledge of elementary teachers in Naga City, 1973-1974 - De la Torre, Heidi Gonzales (1974)
This is an assessment of the health knowledge of the elementary teachers in Naga City during the school year 1973-1974. The researcher found out that, in general, the elementary school teachers revealed a high percentage of inadequacy of knowledge in the five major health areas of the survey instrument administered to them.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Health education (Elementary) -- Naga City